2019
DOI: 10.5539/ibr.v12n4p61
|View full text |Cite
|
Sign up to set email alerts
|

International Standard on Auditing No. 260 and Audit Quality: Evidence from Jordan

Abstract: This study aims to explore the extent of external auditors awareness of the requirements of the International Standard on Auditing No. 260 (Communications with those charged with governance) on audit quality and to shed light on the effectiveness of the communication process based on auditors actual experience. A mixed method approach was employed to achieve the study objectives. The analysis of 116 questionnaires concluded that the requirements of the ISA 260 enhance audit quality, but the two-way communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…As mandated by article 193, paragraph (g) of the Jordanian Corporates Act No. 22 of 1997, 2017, an auditor must present a written statement to the shareholders and applicable parties [46,48]. The audit report must be made in conformity with standard auditing rules, auditing principles, scientific and technical standards [47].…”
Section: Audit Opinion In Jordanmentioning
confidence: 99%
See 1 more Smart Citation
“…As mandated by article 193, paragraph (g) of the Jordanian Corporates Act No. 22 of 1997, 2017, an auditor must present a written statement to the shareholders and applicable parties [46,48]. The audit report must be made in conformity with standard auditing rules, auditing principles, scientific and technical standards [47].…”
Section: Audit Opinion In Jordanmentioning
confidence: 99%
“…Resulting this categorisation, according to the corporates Law 22/1997, 2017 /article (195/b), the auditor must give his final opinion on a company's financial statements (balance sheet and profit and loss account) in one of the following ways: 1) absolute approval (unmodified/unqualified opinion) of the annual sheet, profit, and loss account and cash flow, 2) (unmodified/unqualified opinion), approval with reserve, 3) modified/qualified opinion) of the balance sheet, profit and loss account and cash flow, provided that he states the reasons for such a reservation and its financial effect on the company. and 4) Non-approval (adverse or disclaimer opinion) of the balance sheet, profit, and loss account and cash flows and returning them to the board of directors, with the reasons justifying such a rejection of the balance sheet [48,57].…”
Section: Audit Opinion In Jordanmentioning
confidence: 99%
“…Ironically the percentage of studies with corroborated documentations with the aforementioned observations but, with support to accountability and transparency provided through the instrument of audit far outweigh the opposite. For instance, Hanskamp-Sebregts, et al (2020), Shbeilat (2019), Ozuomba (2019), Ibironke (2019), Adedeji et al (2018), Ogundana et al (2017) are among authors with summation of the significant relationship subsisting between the importance of public sector audit and accountability and transparency.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Moreover, there are additional researches examine the relationship between AC financial expertise and managerial reporting quality in Jordan. [27] discovered a negative relationship between the existence of financial experts on AC and the occurrence of financial restatements in Jordan. [29] and [31] further indicated that AC financial expertise is positively connected with earnings quality in Jordan.…”
Section: Logistic Regression Analysismentioning
confidence: 99%
“…The configuration of AC is less strict in Jordan compared to developed nations [26,27]. Furthermore, in 2004, instituting ACs became obligatory for corporates listed in the Jordan Securities Commission (JSC).…”
Section: Introductionmentioning
confidence: 99%